IMPLEMENTASI STRATEGI PERTUMBUHAN PASCAGEMPA BUMI DALAM BISNIS PENGINAPAN DI KAWASAN WISATA SEMBALUN PULAU LOMBOK - Rusdan Rusdan; Sulhaini Sulhaini; Rahman Dayani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
This research is to explore the lodging bussiness condition of sembalun community after the erthquake in lombok island exactly in the year of 2018, the effect of natural disaster had been paralyzed the lombok island part of northern including the torist area of sembalun. The rarely visitors who come to sembalun area after the earthquake have caused the lodging bussiness are getting down, many hotels are broken, and it could not be repaired until recently and many other also could not be operated while some of hotel which are able to be used have given the little happyness for the owner, could enjoy their income even the condition is not fully good therefore is required the right growth strategy to reincrease the lodging busniss thus the people do not spend the lot of cost in repairing their bussniss and also do not get the wrong step in determine the next step. This research try to give solution to develop the growth strategy as an alternatif which could be selected by the hotel managers in increasing their bussiness in the next.